Clinical Heterogeneity in Patients With FOXP3 Mutations Presenting With Permanent Neonatal Diabetes - Rubio-Cabezas, Oscar (American Diabetes Association, 2009)

(untitled)
OBJECTIVE—Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is caused by FOXP3 mutations. We aimed to determine the prevalence, genetics, and clinical phenotype of FOXP3 mutations in a large cohort with permanent neonatal diabetes (PNDM). RESEARCH DESIGN AND METHODS—The 11 coding exons and the polyadenylation region of FOXP3 were sequenced in 26 male subjects with diabetes diagnosed before 6 months of age in whom common genetic causes of PNDM had been excluded. Ten subjects had at least one additional immune-related disorder, and the remaining 16 had isolated diabetes. RESULTS—We identified four hemizygous FOXP3 mutations in 6 of 10 patients with associated immune-related disorders and in 0 of 16 patients with isolated diabetes (P = 0.002). Three patients with two novel mutations (R337Q and P339A) and the previously reported L76QfsX53 developed classic IPEX syndrome and died within the first 13 months. The novel mutation V408M was found in three patients from two unrelated families and had a mild phenotype with hypothyroidism and autoimmune enteropathy (n = 2) or nephrotic syndrome (n = 1) and survival to 12–15 years. CONCLUSIONS—FOXP3 mutations result in ∼4% of cases of male patients with permanent diabetes diagnosed before 6 months. Patients not only have classic IPEX syndrome but, unexpectedly, may have a more benign phenotype. FOXP3 sequencing should be performed in any male patient with the diagnosis of diabetes in the first 6 months who develops other possible autoimmune-associated conditions, even in the absence of full IPEX syndrome.